Administrative Coercion in the Activity of Law Enforcement Bodies - KEGEMBAYEVA, Zhanar; ABDIKHALIKOV, Abzal (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019, 2019)
This research dwells on the concept, specifics and classification of administrative and legal coercive measures used in the activities of law enforcement bodies. The authors of the article consider legal grounds for their application and the system of bodies applying administrative coercion as two separate phenomena. They also provide general characteristics of the international application of administrative coercive measures and address the issues of applying the chosen measures of administrative and legal coercion. The article aims at analyzing the notions, features and general characteristics of the main administrative coercive measures used in the activities of law enforcement bodies in the Republic of Kazakhstan. The paper presents conclusions and suggestions on the implementation of administrative and legal coercive measures used by law enforcement bodies. In addition, it considers the possibility of utilizing international experience in training employees who apply administrative coercive measures.